PERAN NASKAH AKADEMIK DAN DAFTAR INVENTARISASI MASALAH DALAM MEWUJUDKAN PERATURAN DAERAH NOMOR 2 TAHUN 2015 TENTANG PERLINDUNGAN ANAK YANG ASPIRATIF DI KOTA TANGERANG - Beggy Tamara, Hendra Sudrajat, (Kopertis Wilayah X, 2018)
The rule of law provides guarantees for human rights and popular sovereignty through the constitution. The 1945 Constitution of the Unitary State of the Republic of Indonesia is the highest constitution of Indonesia as the foundation for the implementation of the rule of law of democracy. With the rolling of reforms by amending the constitution to establish new formats of regional government, including the construction of ideal regional regulations. The ideal regional regulation is one that is able to provide solutions to various community problems through binding regulations. The type of research used is normative legal research using a statutory approach or statute approach and a case approach or case approach. the statutory approach or statute approach is to use the regional regulation approach. The establishment of regional regulations is the authority of the Regional People's Legislative Assembly together with the Regional Head, but sometimes raises various problems, namely the role of the regional government more strongly than the people in the process of drafting regional regulations without accommodating the aspirations of the people, including the formation of regional regulations as a form of democracy and participation in the regions. Community participation in the process of forming Regional Regulation Number 2 of 2015 concerning Participatory Child Protection in the City of Tangerang Banten Province is very important to realize a democratic state of law through aspirational regional regulations.